Antioxidant activity of ecoenzyme derived from Siamese orange peel (Citrus nobilis) at different fermentation duration - Anak Agung Ayu Radismarani Putri; Pande Ayu Naya Kasih Permatananda; I Gde Suranaya Pandit; Asri Lestarini (Acta Biochimica Indonesiana)
Background: Ecoenzyme is an organic fermentation product derived from fruit peel waste, offering zero-waste system benefits along with antibacterial, insecticidal, and cleaning properties. Kintamani, a major producer of Siamese oranges (Citrus nobilis) in Bali, generates significant orange peel waste suitable for ecoenzyme production. However, the antioxidant potential of ecoenzymes remains poorly studied.